Northwest history. Mining. Machinery & equipment. 1931-06-16 (1931)
Develop lead mine A portable compressor and other equipment will soon be in operation at the property of the Louise Lead Mines company on Beaver creek in the Delta district of the Coeur d'Alenes, where Mike Savage, Burke McIntosh and Louis Kelpinger are starting development. The drift is now well under way. Hand operations are used until the compressor can be installed.